Divestment and Engagement: The Effect of Green Investors on Corporate Carbon Emissions - Matthew E. Kahn; John G. Matsusaka; Chong Shu (Institute of Labor Economics (IZA), 2023)
This paper studies whether green investors can influence corporate greenhouse gas emissions through capital markets, either by divesting their stock and limiting polluters' access to capital, or holding polluters' stock and engaging with management. We focus on public pension funds, classifying them as green or non-green based on which political party controlled the fund. To isolate the causal effects of green ownership, we use exogenous variation caused by state-level politics that shifted control of the funds and portfolio rebalancing in response to returns on non-equity investment. Our main finding is that companies reduced their greenhouse gas emissions when stock ownership by green funds increased and did not alter their emissions when ownership by non-green funds changed. We find evidence that ownership and constructive engagement was more effective than confrontational tactics such as voting or shareholder proposals. We do not find that companies with green investors were more likely to sell off their polluting facilities (greenwashing). Overall, our findings suggest that (a) corporate managers respond to the environmental preferences of their investors; (b) divestment in polluting companies may be counterproductive, leading to greater emissions; and (c) private markets may be able to address environmental challenges without explicit government regulation.
Keywords: G11; Q54; 330; corporate decarbonization; divestment; engagement; investors